Tribological behaviour of bilayer alumina and mullite plasma-sprayed coatings deposited on a refractory substrate at high temperatures (2023)
Bilayer alumina/mullite and mullite/alumina coatings were sprayed on conventional silico-aluminous refractory bricks by atmospheric plasma spraying. The wear behaviour of these coatings were assessed under sliding contact conditions up to 1000 ◦C through a ball-on-disk test. Afterwards, a set of physical and mechanical properties were evaluated before and after the wear tests, with the aim of correlating these properties with the wear behaviour. The results of the wear tests indicate that when alumina is applied as the top coating, the wear mechanism operating on its surface at 25 and 1000 ◦C is ductile deformation, whereas brittle deformation occurs at 500 and 750 ◦C. When mullite was used as the top coating, brittle deformation was observed at all temperatures evaluated. However, both coatings possess higher wear resistances than the silico-aluminous brick used as substrate, and thus, these coatings potentially offer enhanced protection from the abrasive wearing of nonstructural refractories normally used in furnaces for glass and cement production.